Date fighting and sexual risk behaviours among adolescents attending public schools in Ibadan, Nigeria (2015)
The study seeks to examine the prevalence of date fighting and its role in sexual risk behaviours among 1079 boys and 1211 girls in 22 public secondary schools in Ibadan Nigeria. About 60% (1367) reported to have ever experienced at least a form of date fighting. Risk factors for date fighting in boys include, non use of condom at last sex, (OR: 3.67; 95% Cl: 3.23-4.22) current alcohol usage (OR: 1.67; 95% Cl: 1.99-2.05) belonging to a gang (OR:4.09; 95% Cl: 4.29- 5.95) and multiple sex (OR: 3.39; 95% Cl: 4.20-5.05). Among girls, the risks include multiple sexual partners (OR: 2.44; 95% Cl: 1.67-3.88) history of CSA (OR: 3.01; 95% Cl: 3.23-6.05) hawking after school hours (OR:2.22; 95% Cl: 2.76-5.96). A well designed and integrated psycho-educational intervention regarding date fighting and its inherent association to sexual risk behaviors should be part of the overall adolescent's reproductive health campaign in Nigeria.